فعالية أسلوب الاقتصاد الرمزي في تحسين مهارات الرياضيات لدى تلميذات صعوبات التعلم - AlSayed | السيد, Haitham Mohamed Mofarrej | هيثم محمدود مفرج (Najran University | جامعة نجران, 2023)
The study aimed at determining the effect of applying the token economy on improving the level of mathematical skills for students with learning disability in Najran and finding out the effect of using the token Reinforcer on the use and mathematics skills of student's learning disability. The researcher used the experimental approach as a method of study. The sample of the study (14) students with learning disability in mathematics, sample will be divided equally into experimental group and control group, the data is collected from test the achievement of math skills. A pre- and post-test of mathematical skills has been conducted as a tool for study. | هدف البحث إلى تحديد فعالية تطبيق الاقتصاد الرمزي في تحسين مستوى المهارات الرياضية لتلميذات صعوبات التعلم في نجران، ومعرفة فعالية استخدام الاقتصاد الرمزي في تحسين مهارات الرياضيات لتلميذات صعوبات التعلم. وقد استخدمت الباحثة المنهج شبه التجريبي كمنهج للدراسة وذلك لمناسبته لأهداف الدراسة. وقد تكونت عينة البحث من (14) تلميذة من تلميذات صعوبات التعلم في مادة الرياضيات، تم تقسيمهم بالتساوي إلى مجموعة تجريبية ومجموعة ضابطة، كما تكونت أداة الدراسة من اختبار تحصيل مهارات الرياضيات.